A framework for strategy development - McGinn, John G., 1966-; Treverton, Gregory F.; Isaacson, Jeffrey A. (Jeffrey Alan), 1960-; Gompert, David C.; Bunn, M. Elaine; International Security and Defense Policy Center; National Defense Research Institute (U.S.); Rand Corporation; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 2002)
Many observers have noted that past formulations of American military strategy, such as the "Shape, Respond, Prepare Now" approach that the Department of Defense used from 1997 until 2001, have been longer on philosophy than on practicalities. To address those shortcomings, this report outlines a preliminary framework designed to better link strategy with resource priorities and more accurately frame key investment choices. This report contains the results of a study designed to assist the Department of Defense in its efforts to refine the defense strategy in light of recent experiences and to address expectations about future challenges to U.S. national security. The framework model presented in this report provides a space in which decisionmakers can display strategic options and their inherent tradeoffs, debate the merits of those competing choices, and then decide on a specific strategy.
Introduction -- Articulating Strategic Themes -- Linking Themes to Force Postures and Capabilities -- Forming Strategic Constructs -- Testing the Constructs Against the Future Security Environment -- Refining the Constructs -- Applying the Framework.
"National Defense Research Institute."
Includes bibliographical references (p. 69-73).
Also available on the internet via WWW in PDF format.
Keywords: Military doctrine -- United States -- Planning; National security -- United States -- Planning; United States -- Military policy